Microbial Biodegradation of Sunscreen Agents: Mechanisms, Enzymatic Pathways, and Environmental Implications - Nurtayeva, Aigerim; Rakhmonov, Jasur; Sarykova, Aizada; Rachana, Kong; Kristanti, Risky Ayu (Tecno Scientifica Publishing, 2025)
Environmental contamination from sunscreen ingredients such as oxybenzone and octinoxate has become an increasing concern due to their persistence and toxicity, even at trace concentrations. Continuous sunscreen usage leads to the constant release of these pollutants into the environment, where they can bioaccumulate and resist degradation. The novelty of this review lies in its focused synthesis of recent studies on the microbial and enzymatic degradation mechanisms of sunscreen contaminants, particularly oxybenzone and octinoxate, which exhibit high persistence and bioaccumulative potential. Microbial degradation offers a promising biological approach for the breakdown of these organic pollutants, as microorganisms have demonstrated strong biodegradative capabilities toward various environmental contaminants. This process relies on microbial enzymes that transform or mineralize pollutants into less toxic and simpler compounds. Key enzymes involved include laccase, cytochrome P450, and monooxygenase, which catalyze oxidation, reduction, and hydroxylation reactions. The article further examines these organic pollutants in terms of their persistence, environmental occurrence, degradation mechanisms, and pathways, while also addressing their ecological and health impacts. Moreover, different microbial-based treatment technologies are evaluated, highlighting their respective strengths and limitations. Finally, the review emphasizes the need for continued research into organic pollutant behavior and bioremediation technologies to deepen understanding and mitigate the adverse effects of these contaminants on the environment.